APPLICATION OF ELASTIC FOAMPOLYURETHANE FOR THE TREATMENT OF MEAT INDUSTRY WASTEWATER - Lukashenko, S.; Syrovatskyy, O.; Karahiaur, A. (Municipal economy of cities. Series: «Economy science», 2025)
Meat industry enterprises consume large amounts of clean water for production needs. Wastewater from these enterprises, which accounts for 30-40% of water consumption, is significantly contaminated with organic compounds, especially fats and suspended solids with concentrations from 50 to 2000 mg/l or more, the chemical oxygen demand (COD) of these effluents is 1000 - 2600 mg/l. The local treatment facilities available at the industry enterprises - grease traps, settling tanks and flotation tanks do not always provide the required quality of wastewater treatment. For example, the fat content sometimes exceeds the established standards (20-100 mg/l) several times, which subsequently negatively affects the efficiency of municipal wastewater treatment facilities - especially biological ones. In addition, local treatment systems are costly and require significant areas for placement, which is not always acceptable in production conditions. Methods of additional wastewater treatment by filtration through granular loading made of various materials have not found practical application in meat industry enterprises due to the lack of effective methods for regenerating the filter layer. The authors conducted laboratory research to study processing industrial fat-containing wastewater from the meat industry using elastic polyurethane foam. This filter material has the required porosity, sufficient mechanical strength and chemical resistance. Porous polyurethane foam is elastic and has high resilience. This property of polyurethane foam makes it possible to remove the bulk of absorbed contaminants from it mechanically by squeezing, after which it can be reused. During the research, the effect of the size, density, the height of the filter loading, as well as the filtration rate, on the efficiency of treatment from fats and suspended solids was conducted. When selecting the granule sizes, density, and loading height, minimum losses in the filter layer were considered for maximum filtration duration and minimum regeneration time was ensured. Based on the conducted research, the main process parameters for cleaning fat-containing wastewater from the meat industry by filtration were determined: filter layer height - 2 m; filter loading density - 50-60 kg/m3; granule size of the loading 20×20×20 mm; average filtration speed - 5-10 m/h. The fat content during wastewater treatment from the meat industry is reduced to 50-65 mg/l. It was found that it is advisable to regenerate the loading by mechanical pressing on steel drums with a diameter of 150 mm at a pressing zone temperature that ensures the fluidity of organic matter. Implementing the developed technology will ensure the required degree of industrial wastewater purification from meat processing plants when discharged into the urban sewer network. At the same time, a high degree of ease of operation of the unit and its compactness are ensured compared to traditional technologies